SIXTY YEARS OF TROPICAL FORESTRY SCIENCE AT GADJAH MADA UNIVERSITY: A SCOPUS-BASED BIBLIOMETRIC STUDY - Serge Nanda Silatsa; Dwiko Budi Permadi; Takahiro Fujiwara (Indonesian Journal of Forestry Research, 2026)
This Study undertakes a comprehensive bibliometric analysis to explore the research trends in the Scopus publications affiliated with the Faculty of Forestry at Gadjah Mada University (FF-UGM) in the generation of knowledge in tropical forestry. A total of 725 publications affiliated with FF-UGM were mined from the Scopus database and analyzed using VOSviewer and CiteSpace. The findings indicate a steady growth in the number of research publications and therefore, the cumulative count of 5,409 citations amounts to an average of 7.5 citations per publication. Furthermore, FF-UGM has engaged collaborations with researchers from all continents, with Japan exhibiting the highest network power through 112 collaborations. In relation to the sources of funding, a total of 518 articles has been granted financial assistance from 159 donors on a global scale, with 133 publications being self sponsored by UGM. The Burst analysis, further, reveals emerging research frontiers to be explored further in future study including deforestation, catchments, agroforestry, and sustainable development. Thematic clustering indicates five big areas with high interdisciplinary approach to forest management, policy, product innovation, silviculture, and biodiversity conservation. The present bibliometric analysis proves that the FF UGM is also changing its areas of interest into sustainable tropical forest ecosystems and serves as a source of both science and policy-related studies.